Increasing the profitability of the agricultural market by optimizing grain transportation (Economics and region, 2023)
Goal. Finding opportunities to optimize each model series of hopper dispensers, intended for profitable transportation of grain and grain crops, in the conditions of globalization of the agricultural market and intensifying competition in the railway rolling stock market. Methodology. The sequence of solving the one-dimensional problem of substantiating the optimal model series and approaches to clarifying the results in complicated conditions related to the unification of products for the specialization of each division of the appropriate level in the performance of a narrow range of functions regarding the organization of production for the introduction of innovations regarding the special shape of the body of hopper cars for transportation of grain and grain crops. The results. The components of the calculation of costs for development, testing and production and the cost of production of new products are considered, as well as the value of the optimal range of modifications of hopper-dispensers for grain and grain crops. The sequence of creation of flexible production systems as an innovative leap in the development of hopper wagons for grain transportation for the introduction of innovations while increasing production volumes is presented. Novelty. The scientific approaches to determining the essence of the product range are generalized by means of a critical understanding of the process of expanding the range of products with the aim of using excess production capacities while satisfying the needs of consumers more fully at the same time. Practical significance. To meet the growing needs of consumers, a justified line of modifications of hopper dispensers for grain and grain crops with a special body shape. Work was carried out to eliminate gaps both in the assortment and in the depth of the product range of hopper wagons. In the conditions of large-scale production, subject-specialized lines with rigid and flexible connections have been created. The technological process of manufacturing welded structures of hopper cars provides for both differentiation and concentration of the operations performed, taking into account the rhythm and cycle of the entire production process. The production of transverse beams is carried out on semi-automatic one-piece direct-flow lines with flexible connection to several workstations.
Keywords: profitability; model; row; optimization; hopper-dispenser; grain; grain crops